UNCOVERING THE BARRIERS TO TEACHING FACTORY IMPLEMENTATION IN MACHINING VOCATIONAL SCHOOLS - Nurholisoh, Nurholisoh; Putra, Ricky Cahyasari; Ikhsanudin, Ikhsanudin (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2025)
The implementation of the Teaching Factory in Vocational High Schools (SMK) specializing in Machining Engineering is crucial for bridging the gap between schools and industry; however, its application still faces various challenges. This study aims to identify the barriers to Teaching Factory implementation in SMK Machining Engineering programs. The method employed is a Systematic Literature Review (SLR) with a descriptive qualitative approach, analyzing six scientific articles published between 2020 and 2025, selected through the PRISMA protocol. The results indicate that the main barriers lie in managerial aspects (67%), workshop/laboratory facilities (50%), human resources (50%), learning patterns and promotion (33%), as well as products and industry collaboration (17%). Managerial barriers are the most dominant. In conclusion, the implementation of Teaching Factory in SMK Machining Engineering remains suboptimal and requires strengthened management, improved human resources, enhanced facilities, and stronger industry collaboration to support sustainable production-based learning. Therefore, it is recommended to establish a Teaching Factory management team, and develop a data-based evaluation system.